Comparison of Human Papillomavirus Genotypes in Penile Intraepithelial Neoplasia and Associated Lesions: LCM-PCR Study of 87 Lesions in 8 Patients. (May 2020) - Fernández-Nestosa, María José; Guimerà, Nuria; Sanchez, Diego F.; Cañete-Portillo, Sofía; Lobatti, Antonella; Velazquez, Elsa F.; Jenkins, David; Quint, Wim; Cubilla, Antonio L.
Penile intraepithelial neoplasia (PeIN) is currently classified in human papillomavirus (HPV)- and non-HPV-related subtypes with variable HPV genotypes. PeINs are frequently associated with other intraepithelial lesions in the same specimen. The aim of this study was to detect and compare HPV genotypes in PeINs and associated lesions using high-precision laser capture microdissection-polymerase chain reaction and p16 INK4a immunostaining. We evaluated resected penile specimens from 8 patients and identified 33 PeINs and 54 associated lesions. The most common subtype was warty PeIN, followed by warty-basaloid and basaloid PeIN. Associated lesions were classical condylomas (17 cases), atypical classical condylomas (2 cases), flat condylomas (9 cases), atypical flat condylomas (6 cases), flat lesions with mild atypia (12 cases), and squamous hyperplasia (8 cases). After a comparison, identical HPV genotypes were found in PeIN and associated lesions in the majority of the patients (7 of 8 patients). HPV16 was the most common genotype present in both PeIN and corresponding associated lesion (50% of the patients). Nonspecific flat lesions with mild atypia, classical condylomas, and atypical condylomas were the type of associated lesions most commonly related to HPV16. Other high-risk HPV genotypes present in PeIN and associated nonspecific flat lesion with mild atypia were HPV35 and HPV39. In this study of HPV in the microenvironment of penile precancerous lesions, we identified identical high-risk HPV genotypes in PeIN and classical, flat, or atypical condylomas and, specially, in nonspecific flat lesions with mild atypia. It is possible that some of these lesions represent hitherto unrecognized precancerous lesions.